Customer Satisfaction In High Demand And Low Supply Of Vegetable Oil In Indonesia - Yosua Amendson Pupella; Nurdayadi Nurdayadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Vegetable oil is a type of oil that is produced from plants like palm, sunflower, and even soybean. This oil can be used as cooking oil, bio-fuel, or some other product like cosmetics. When the Covid-19 pandemic hits, the production of vegetable oil decreased but was still able to fulfill the domestic demand. In the year 2022, a war involving Ukraine, the largest producer of sunflower oil, has decreased the supply of vegetable oil while the demand is still increasing. This quantitative research analyzes customer satisfaction of vegetable oil users during the low supply and high demand environment. 100 respondents who cook using vegetable oil in Indonesia have completed the survey with a response rate of 83.33%. This research also analyzes the relationships between price, product availability, and government rules regarding customer satisfaction. The result shows that price, product availability, and government rules influence customers positively. The measurement of the government rules variable lacks reliability, and a more specific measurements are needed to increase understanding of the effect of government rules on customer satisfaction.